Linking Socioeconomics to Biodiversity in the City: The Case of a Migrant Keystone Bird Species - Villaseñor, Nélida R.; Escobar, Martín A. H. (Frontiers in Ecology and Evolution, 2022)
Billions of wild animals migrate every year between breeding and non-breeding sites, facing new environmental conditions due to anthropogenic change. Although cities engender profound environmental changes, they provide habitat for some migratory birds contributing to conserving biodiversity and restoring human-nature connections. A common issue in Neotropical cities is their socio-environmental segregation, that might result in wealthier people having access to greater biodiversity in their neighborhoods. Although growing evidence shows a relationship between wealth and biodiversity in cities, it remains poorly investigated in relation to animals, particularly migratory birds. We present the first study on the effects of socioeconomic status on a Neotropical austral migrant considered a keystone species. We tested whether neighborhood socioeconomic category and habitat variables relate to the occurrence of the Green-backed Firecrown hummingbird in its overwintering habitat in urban areas. We hypothesized that higher socioeconomic status of neighborhoods would positively influence hummingbird occurrence through mediating effects of woody plant cover. We found that hummingbird occurrence increased with socioeconomic level of neighborhoods and woody cover. Specifically, we found that socioeconomic level influenced hummingbird occurrence indirectly through woody and shrub cover. We also found a direct effect of socioeconomic level on hummingbird occurrence suggesting the need for further research. Our findings show that wealthier neighborhoods exhibit greater woody cover and higher hummingbird occurrence than poorer neighborhoods, providing dissimilar opportunities to experience nature close to home. In neighborhoods where people of lower socioeconomic status live, strategies aiming to increase tree and shrub cover will promote a more environmentally just city.